ANALISIS PENGARUH PERIKLANAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA CV VISTA ESTATE MEDAN - Lili Suryati (Politeknik Negeri Sriwijaya, 2013)
The purpose of this study is to investigate and analyze the influence of advertising on purchase decisions at CV Vista Estate Medan. The method used in this study is the survey approach, and the research type is descriptive quantitative. Method of data collection uses a list of questions (questionnaire). Data analysis method used is simple linear regression, the coefficient of determination test and t-test. The samples are customer of CV Vista Estate, is about 53 people. Based on the results of the study showed that the coefficient of determination (R Square) of 0.428, which means that the independent variable (advertising) has an influence about 42.8% on the dependent variable (purchase decisions) and 57.2% more influenced by other variables not be included in this study. While the hypothesis testing with a t-test shows that tcount > ttable(6.178> 2.01) at α = 2.5%. It can be concluded that the advertising variable positive and significant impact on purchasing decisions. The relation between advertising and purchase decision is shown by formula Y = 7,066 + 0,814 X